MODEL PEMBELAJARAN PENDIDIKAN INTERPROFESSIONAL: TINJAUAN SISTEMATIK: Learning Model for Interprofessional Education: A Systematic Review - Tri Ayu Yuniyanti; Andi Masyitha Irwan (LPPM STIKES Pemkab Jombang, 2022)
Introduction: Interprofessional education (IPE) emphasizes the importance of collaborative practice that can be achieved through teamwork between two or more healthcare professionals. This systematic review aims to explore more about IPE learning models. Method: The search is using electronic data base from a journal that has been published through PubMed, Science Direct and Wiley. Result: based on the review of the 12 selected journals, the learning models of IPE used is exchange-based (n = 6); action-based (n = 5); simulation-based (n = 4); and practice-based (n = 2). Discussion: various models of IPE can be used According to the learning outcomes. IPE has a positive overall impact on improving students knowledge and skills on interprofessional roles and responsibilities, communication, team and teamwork.